Calcium isotope fractionation in sedimentary pore fluids from ODP Leg 175: Resolving carbonate recrystallization. (1st September 2018) - Bradbury, Harold J.; Turchyn, Alexandra V.
Abstract: We present calcium isotope data from pore fluids and solids from Ocean Drilling Program Leg 175: Sites 1081 and 1086 (off the coast of West Africa). These sites are similar with respect to geographic location, sediment age (from modern to 8 Myr), and water depth (800 m), but Site 1081 is carbonate-poor, whereas Site 1086 is carbonate-rich. Therefore, these sites are suited for the exploration of the influence of sediment type on carbonate dissolution, precipitation, and recrystallization. We use two numerical modelling approaches to explore the rates of carbonate dissolution and precipitation in the sediment column. The first is the standard diffusion-reaction approach, using the strontium concentration within the pore fluid to ascertain a dissolution rate for the carbonate, which is then applied to a second model of calcium isotopes within the pore fluid to calculate precipitation rates. Given the high sedimentation rates we also apply an advection-reaction model (Huber et al., 2017) which results in the same depth distribution of carbonate precipitation but significantly higher overall rates, which is discussed. Calcium isotope ratios in pore fluid calcium increase in zones where our model predicts carbonate precipitation, and approach isotopic equilibrium with the solid in zones where our model predicts equivalent rates of dissolution and precipitation, similar to previous findings. Contrary to previous findings in marine sediments, our model requires a calcium isotope fractionation on carbonate precipitation to fit the data, as there is an offset between the δ 44 Ca of the fluid and the solid. Using the zones of carbonate precipitation determined from the models and previously published carbon isotope profiles of the dissolved inorganic carbon from these sites, we suggest that the δ 13 C of the authigenic carbonate is uniformly lower than biogenic carbonate but by a wider range than was previously suggested.